Determinan Profitabilitas pada Bank Konvensional di Indonesia - Sari, Sayu Made Ratna; Nurdiawansyah, Nurdiawansyah (Politeknik Ganesha Medan, 2024)
Increased economic growth in Indonesia is not always accompanied by increased profitability in the banking sector in Indonesia, this can be caused by various factors. This survey aims to provide the effect of non-performing financing, liquidity, and BOPO on profitability. The sample of this study is 204 data points from 72 conventional banks listed on the IDX and official banking websites during the period 2020 - 2022, through the purposive sampling method. Descriptive with a quantitative approach is the type of method used. Multiple linear regression analysis using the test tool, SPSS 18, is a technique that is applied in analysis. This study’s findings suggest that partially the LDR variable shows a positive as well as significant effect on profitability in conventional banks in Indonesia. Meanwhile, partially the NPL and BOPO variables shows a negative as well as significant effect for profitability in conventional banks in Indonesia. The effect of independent variables, according to the coefficient of determination of 82.8% can affect ROA, while the other 17.2% is influenced variables outside the research model.